Performance of sulfided NiMo catalyst supported on pillared bentonite Al and Ti under hydrodeoxygenation reaction of guaiacol - Rinaldi, Nino; Sari, Novi Liana; Sumari, S.; Kristiani, Anis; Agustian, Egi; Widjaya, Robert Ronald; Dwiatmoko, Adep (Center of Biomass & Renewable Energy (CBIORE), 2024)
Bio-crude oil is known to be sustainable, eco-environmentally, and an alternative energy source produced by biomass pyrolysis. However, its quality remains relatively low due to a higher oxygen concentration compared to liquid fuels from fossils. Therefore, an upgrading process is necessary through the catalytic hydrodeoxygenation (HDO) process. This work synthesized pillared bentonite using Al and Ti metals as the pillaring agent to produce Al-PILC and Ti-PILC as catalyst support for sulfided NiMo. Their catalytic activity in HDO reaction using guaiacol as a model compound of bio-crude oil were also evaluated. Characterization of the bentonite-pillared materials, including Al-PILC, Mo/Al-PILC, NiMo/Al-PILC, Ti-PILC, Mo/Ti-PILC, and NiMo/Ti-PILC, was performed using Surface Area Analyzer, X-ray Diffractometer (XRD), Temperature-Programmed Desorption of ammonia (NH3-TPD), X-Ray Fluorescence (XRF), and Scanning Electron Microscope (SEM) techniques. The characterization results confirm the pillarization process of bentonite using Al and Ti metals as the pillaring agent, and the preparation of the NiMo catalyst using the stepwise impregnation method was successfully prepared. The NiMo/Ti-PILC catalyst performs a superior conversion value on the HDO guaiacol reaction than other catalysts. A well dispersion of Mo and Ni metals on the surface support (NiMo/Ti-PILC), thus creating numerous active sites of the catalyst after the sulfidation. Variations in time and temperature during the HDO guaiacol reaction significantly affected the conversion.